ANALISIS PENGARUH DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA PEMERINTAH DAERAH KOTA SEMARANG - Hakimah, Siti Hasna Zahra; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2024)
This study aims to determine whether the General Allocation Fund (DAU), Regional Original Income (PAD) affects the Regional Expenditure of Semarang City. The method of analysis used is quantitative method, with multiple regression testing by doing the classical assumption test before getting the best research model. The variables in this study are General Allocation Fund (DAU), Regional Original Revenue (PAD) as independent variables, while the dependent variable is Regional Expenditure. The population used in this study is the Semarang City Regional Revenue and Expenditure Realization Report 2016 - 2022. The object of this research is the General Allocation Fund (DAU), Regional Original Income (PAD) and Regional Expenditure (BD). The sample used is the Semarang City Regional Revenue and Expenditure Realization Report 2016-2022. The data analyzed in this study are time series data sourced from the Central Bureau of Statistics and the Semarang City Financial and Asset Management Agency.The results of this study prove that the General Allocation Fund has no significant effect on regional expenditure in Semarang City, Regional Original Revenue has a significant effect and has a positive influence on regional expenditure in Semarang City.